STAKEHOLDERS’ PARTICIPATION IN SCHOOL IMPROVEMENT PLAN AND SCHOOL PERFORMANCE OF SECONDARY SCHOOLS - Guzman, Jaypee (International Journal of Arts, Sciences and Education, 2022)
The quantitative approach, particularly correlational research design, was used to assess the extent of stakeholders' participation in the School Improvement Plan preparation, implementation, monitoring, and evaluation and its connection to school performance. There are 75 participants in the study who are composed of 15 heads of school, 15 teachers, 15 students, 15 officers of the PTA, and 15 officers of the Barangay. These participants are members of the school's planning team. The questionnaire serves as the principal instrument of the analysis. The data analysis was carried out using ANOVA and Pearson r: frequency, percentage, and weighted mean. The study results revealed that the stakeholders have a significant degree of involvement in the School Improvement Plan preparation, implementation, monitoring, and evaluation. Further results indicate that school performance is very good, and it does not differ regardless of the type of school. Surprisingly, they still faced challenges despite the large extent of stakeholders' involvement in the three stages of the School Improvement Plan. There is no significant difference in terms of the degree to which the different stakeholder groups engage in the three stages of the school improvement plan and type of school. Also, the same result was found that there was no significant difference between the performance of the school and the type of school. Another finding using the Pearson r revealed that there is no significant relationship between the extent of stakeholders’ participation in the three stages of the School Improvement Plan and school performance. This suggests that the degree of stakeholders' involvement may not guarantee a very high school performance.